Perbandingan Kepuasan Kerja Pegawai Pada Dinas Peternakan dan Kesehatan Hewan dengan Dinas Pertanian dan Perkebunan Kabupaten Bima - Tria Miranty; Muhammad Ali (Journal of Business and Economics Research (JBE), 2020)
Human resources are the key to success in Animal Husbandry and Health Services with the Department of Agriculture and Plantation Bima. The phenomenon of employee job satisfaction is not optimal and mistakes made by employees become one of the problems in service. This study aims to determine the comparison of job satisfaction between the two agencies, the number of samples used as many as 100 samples with each of 50 respondents, it is known that job satisfaction of employees in the two offices has a difference. With this study, it can be seen how satisfied employees in the work. This type of research is comparative. While data collection techniques are observation, documentation, and questionnaire. The data collected was analyzed using a sample t-test. This test is used to determine differences in job satisfaction of employees in the Department of Animal Husbandry and Animal Health and the Department of Agriculture and Plantation Bima